If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-7=-3y-19
We move all terms to the left:
3y-7-(-3y-19)=0
We get rid of parentheses
3y+3y+19-7=0
We add all the numbers together, and all the variables
6y+12=0
We move all terms containing y to the left, all other terms to the right
6y=-12
y=-12/6
y=-2
| (2/3)(1+n)=(-1/2n) | | r-71/5=3 | | 87-v=275 | | D/5+7=4-2d/3 | | 1+p=8 | | x/4+x/3=2/3 | | .75x+16=28 | | 7x/12=2/3 | | 34/a=40/100 | | 6n=6.23 | | 3(2c–5)–4(2–c)=3(4c–5) | | 3.2g+2.8+2g=2.5g-1.2 | | (y/6)+(y/5)=(6/7) | | 7x=0.164 | | y6+y5=67 | | 7v-8v=7 | | 7x=3.72 | | y/6+y/5=6/7 | | 7x=1.903 | | -2y+-12=3y+3 | | 2n-15=11 | | y6+y5=67y6+y5=67 | | 7/9x+6/9=1/9x | | .75x-16=28 | | 15-2n=11 | | 3(x2+4)+5x=2x2+6(x+3) | | 15n-2=11 | | 1/6x+4/3=20 | | y/2=y/3=1 | | X+9y=167 | | 3t-(2t+8)=9 | | 9-2k-3)=k |